Probabilistic health risk assessment of zinc oxide nanoparticles from consumer products in adult populations. Issue 1 (22nd November 2022) - Mu, Yunsong; Li, Xiang; Chen, Peihan; Pang, Chengfang; Wu, Fengchang; Giesy, John P.; Chang, Huazhen; Zeng, Fangang
Abstract : A probabilistic approach is established to estimate the risks of n-ZnO from consumer products to human health and associated uncertainties, which provides a foundation for supporting democratic decision-making in governing emerging technologies. Abstract : Zinc oxide nanoparticles (n-ZnO) are one of the most ever-increasing utilized nanomaterials in consumer products. Due to their antibacterial properties and superior efficiency in absorbing ultraviolet radiation, they are widely used as additives in food packaging and sunscreens. There is thus a need for scientific understanding of risks to the health of adult populations associated with n-ZnO. However, due to inadequate data in relation to characterizing hazards and exposure, there is a substantial uncertainty in risk assessment. In the present study, probabilistic approaches, including Monte Carlo and bootstrap methods, were integrated to assess the relative uncertainties and risks of n-ZnO to the health of males and females. Two major exposure pathways, oral from food packaging and percutaneous from sunscreen-based comestics, were evaluated by considering the uncertainty and variability involved in the exposure assessment. Given the cumulative uncertainties of all the extrapolation factors, the results showed that the individual margin of exposure (IMoE) of n-ZnO exhibited a minimal risk through oral exposure, with a minimum value of 786 for males and 96.2 for females (5th centile). However, within the entire range of IMoE values by Monte Carlo simulation through dermal exposure, the IMoE values in 11.45% of exposure scenarios for males and 18.87% for females were lower than the upper limit of the acceptable risk (IMoE ≤ 1). Intra-species, inter-species, and subacute-to-chronic extrapolation factors in the hazard assessment process contributed up to 97% of the uncertainty. These findings provided a scientific basis for understanding risks to the health of adult populations that could help allow regulatory acceptance of consumer products containing n-ZnO and highlighted the need for additional studies on hazard and exposure assessments of nanotechnologies.